Technical Barriers and Development of Cu Wirebonding in Nanoelectronics Device Packaging. (2nd October 2012) - Gan, C. L.; Ng, E. K.; Chan, B. L.; Hashim, U.; Classe, F. C.
Abstract : Bondpad cratering, Cu ball bond interface corrosion, IMD (intermetal dielectric) cracking, and uncontrolled post-wirebond staging are the key technical barriers in Cu wire development. This paper discusses the UHAST (unbiased HAST) reliability performance of Cu wire used in fine-pitch BGA package. In-depth failure analysis has been carried out to identify the failure mechanism under various assembly conditions. Obviously green mold compound, low-halogen substrate, optimized Cu bonding parameters, assembly staging time after wirebonding, and anneal baking after wirebonding are key success factors for Cu wire development in nanoelectronic packaging. Failure mechanisms of Cu ball bonds after UHAST test and CuAl IMC failure characteristics have been proposed and discussed in this paper.